2014
DOI: 10.2527/jas.2013-6743
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nursery feeding program on subsequent growth performance, carcass quality, meat quality, and physical and chemical body composition of growing-finishing pigs1

Abstract: An experiment was conducted to examine the effect of the nursery feeding program on subsequent growth performance, carcass quality, meat quality, and physical and chemical body composition of growing-finishing pigs. Four dietary treatments were used in a 2 × 2 factorial arrangement of treatments based on diet complexity (Complex vs. Simple) and in-feed antibiotics (2,730 [+AB] vs. 0 [-AB] mg of chlortetracycline /kg].A total of 552 pigs, in 5 blocks, were weaned at 21 ± 2 d of age with an initial BW of 7.03 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 32 publications
7
32
1
1
Order By: Relevance
“…At present, information on the effects of EAI on subsequent growth performance under different dietary CP levels is limited. Skinner et al [ 25 ] reported that the use of antibiotics (therapeutic dose usage) in the nursery diets with normal-CP level appeared to reduce subsequent ADG of the pigs as compared to non-treated controls. In the present study, the antibiotics at low dosage did not have effect on subsequent ADG with normal-CP diet, though increased the subsequent ADG under low-CP diet.…”
Section: Discussionmentioning
confidence: 99%
“…At present, information on the effects of EAI on subsequent growth performance under different dietary CP levels is limited. Skinner et al [ 25 ] reported that the use of antibiotics (therapeutic dose usage) in the nursery diets with normal-CP level appeared to reduce subsequent ADG of the pigs as compared to non-treated controls. In the present study, the antibiotics at low dosage did not have effect on subsequent ADG with normal-CP diet, though increased the subsequent ADG under low-CP diet.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that AGP supplemented pigs had better recovery of weight and feed intake after LPS challenge than those supplemented with yeast extract. Weber et al [24] and Skinner et al [25] reported that AGP improves ADG during the nursery phase, whereas Wu et al [26] reported that piglets receiving in-feed AGP and challenged with enterotoxigenic E. coli had higher ADG and G:F than control. Niewold [27] suggested that AGP improve gut health and growth performance of livestock by reducing the gut pathogen load and competition for nutrients between the host and gut microbes.…”
Section: Discussionmentioning
confidence: 99%
“…All sources but one utilized off-site nursery and finishing, while the other was farrow-to-finish for Cohort 1 and off-site finisher for Cohort 2. Pigs received either a standard high-complexity (HC) nursery diet or experimental lower-cost, low-complexity (LC) diet in which the majority of the animal protein was replaced with plant protein throughout the nursery phase (13). The diets for all pigs were the same at all other production stages.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the composition of nursery diets, particularly protein content and quality, may affect animal health, carcass quality, and growth rate (12). Nursery diets that substitute animal proteins with plant-based proteins may decrease costs associated with pork production without sacrificing meat quality or body weight (13) but the effects these diets may have on antibody responses, if any, are not yet fully understood (14).…”
Section: Introductionmentioning
confidence: 99%